FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PENYAJIAN INFORMASI AKUNTANSI (PADA PT BRI DI KOTA MAGELANG) - Anugraheni Dyah Nastiti; Ririh Dian Pratiwi (MEDIA, 2013)
The quality of information presentation accounting holds important role in financial institition such as bank to be balanced with the role of human resources are inside them. Research purpose this is to see if education, training, and job experience effect of the quality of information presentation for PT. Bank Rakyat Indonesia Tbk in the town. Benefits from this research is improving human resources seen from education variable, training, and job experience in conveying quality information presentation of accounting for companies to be more significant and in recruting employee can more significant and more selected. Population research used 16 office units and 1 BRI Branch Office in town Magelang. How to use the media data collection questionnaire to collect primary data. The respondents of this study is the teller of the accounting staff available at the Branch Office and the Office of BRI Units with a population taking as many as 34 samples of data that can be processed. The analysis method used is the method of multiple regression analysis (Multiple Regression Analysis), using Spearman-Rank test validity and reliability of test-Alpha Croanbach processed using SPSS 16. The results of the analysis showed that education, training, and work experience have positive simultaneously or partially on the quality of the presentation of accounting information.